Functional capacity and level of physical activity in centenarians of Florianópolis, Brazil - Inês Amanda Streit; Artur Rodrigues Fortunato; Eduardo Hauser; Giovana Zarpellon Mazo (Revista da Educação Física)
Aim: To compare the level of physical activity and functional capacity of centenarians from Florianópolis, Brazil. Methods: To measure the level of physical activity and functional capacity, pedometer and the Katz scale, respectively, were used. Study participants were 23 centenarians (101.7 ± 2.0 years). Results: An average of 641.23 (SD = 655.83) steps/day among subjects was observed. Although independent centenarians (n = 15) presented higher average number of steps/day (813.53, SD = 715.97) compared to dependent ones (n = 8) (318.15, SD = 378, 98), no statistically significant difference was observed (U = 33.000, p = 0.087). Conclusions: the level of physical activity of dependent and independent centenarians did not differ statistically. Nevertheless, descriptive analysis shows that the number of steps was higher in independent centenarians, suggesting that they may have a more active lifestyle.